Scientific and practical training component of higher education applicants by implementing the digitalization of the information space - Tverytnykova, Elena; Demidova, Yu. Ye.; Salata, Halyna (Національний технічний університет "Харківський політехнічний інститут", 2023)
The article deals with the problem of forming a competent understanding of students' scientific research work as a component of the training specialists system in the technical field. The main attention is paid on the experience of technical universities in Ukraine in the implementation of various forms of the scientific research work in the educational process. It is proved that the students’ scientific research work has a two-level end-to-end character. The expectations of respondents regarding the implementation of different forms and methods of the scientific research work into the educational process are described. The self-evaluation of bachelors was based on the personal experience of students participating in various types of scientific activities. The historical experience of introducing forms and methods of student scientific research work based on the use of archival statistical materials is investigated. It is emphasized that the new conditions that have arisen with the spread of the COVID-19 pandemic and the full-scale war started by the russian federation have made certain changes to the conduct of scientific activities with students. It is necessary to revise approaches to its organization in order to integrate into the globalized information society.

У статті розглянуто проблему формування компетентного розуміння студентами науково-дослідницької роботи як складової системи підготовки фахівців технічного профілю. Основну увагу приділено досвіду технічних університетів України щодо впровадження різноманітних форм науково-дослідної роботи в навчальний процес. Доведено, що науково-дослідна робота студентів має дворівневий наскрізний характер. Розроблено структурно-логічну схему наскрізного виконання науково-дослідної роботи студентів. Охарактеризовано очікування респондентів щодо впровадження в навчальний процес різних форм і методів науково-дослідної роботи. Самооцінка бакалаврів базувалася на особистому досвіді студентів, які займаються різними видами наукової діяльності. Вивчено історичний досвід впровадження форм і методів науково-дослідної роботи студентів на основі залучення архівних статистичних матеріалів. Закцентовано увагу на тому, що нові обставини, які виникли з розповсюдженням пандемії COVID-19 та розв'язаною російською федерацією повномасштабною війною внесли певні корективи і до проведення наукової діяльності зі студентами. Ситуація викликала потребу переглянути підходи до її організації з метою інтеграції до глобалізованого інформаційного суспільства.
Науково-практична складова підготовки здобувачів вищої освіти через імплементацію цифровізації інформаційного простору
Keywords: archive; documents; electronic resources; information space; архів; документи; електронні ресурси; інформаційній простір